Case report: Autoimmune glial fibrillary acidic protein astrocytopathy misdiagnosed as tuberculous meningitis - Qin, Ningxiang; Wu, Xingguo; Wang, Jing; Wang, Wei; Wang, Xuefeng; Ma, Yuanlin; Wang, Liang (Frontiers in Neurology, 2023)
Introduction Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a new form of autoimmunity-mediated central nervous system disease. It is especially easy to misdiagnose when clinical symptoms and cerebrospinal fluid (CSF) indicators are similar to those observed in patients with tuberculous meningitis (TBM). Methods We retrospectively analyzed five cases of autoimmune GFAP astrocytopathy that were initially misdiagnosed as TBM. Results In the five reported cases, all but one patient had meningoencephalitis in the clinic, and all patients exhibited increased pressure, lymphocytosis, increased protein levels, and decreased glucose levels in their CSF results and did not have typical imaging findings of autoimmune GFAP astrocytopathy. TBM was the initial diagnosis in all five patients. However, we found no direct evidence of tuberculosis infection, and anti-tuberculosis treatment had inconclusive effects. Following a GFAP antibody test, the diagnosis of autoimmune GFAP astrocytopathy was made. Conclusion When there is a suspected diagnosis of TBM but TB-related tests are negative, the possibility of autoimmune GFAP astrocytopathy should be considered.